2021
DOI: 10.11648/j.ejb.20210902.14
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Diversity in Smallholder Coffee Farms of Bedeno District, Eastern Hararghe Zone, Oromia Regional State, Ethiopia

Abstract: Although, Coffee agroforestry have a considerable contribution in supporting biodiversity, yet their contribution are insufficiently documented. Thus, this study was aimed to assess the diversity tree species in small holder coffee farms in Bedeno district, East Hararghe Zone, Oromia Regional State, Ethiopia. Eleven kebeles were selected purposively and four of them were randomly selected from which 119 households were selected, whose coffee farms used for Tree inventories in this study. The study was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Our results further showed that Moraceae (33.3%) and Fabaceae (26.7%) were the most common families in Kaweri Coffee Plantation (Table 1), agreeing with observations in other coffee agroforestry systems of Uganda (Negawo & Beyene 2017) and elsewhere (Soto-Pinto et al 2001;López-Gómez, et al 2008;Zekwan et al 2021). Solanum giganteum Jacq., locally known as 'setaaba' was the most abundant shrub (19.8 shrubs/ha) whereas, the most abundant shade tree species were Albizia chinensis Osb.…”
Section: Shade Tree Species Composition and Abundancesupporting
confidence: 92%
“…Our results further showed that Moraceae (33.3%) and Fabaceae (26.7%) were the most common families in Kaweri Coffee Plantation (Table 1), agreeing with observations in other coffee agroforestry systems of Uganda (Negawo & Beyene 2017) and elsewhere (Soto-Pinto et al 2001;López-Gómez, et al 2008;Zekwan et al 2021). Solanum giganteum Jacq., locally known as 'setaaba' was the most abundant shrub (19.8 shrubs/ha) whereas, the most abundant shade tree species were Albizia chinensis Osb.…”
Section: Shade Tree Species Composition and Abundancesupporting
confidence: 92%